EVALUATION OF PRODUCTIVE PERFORMANCE OF JAPANESE QUAIL IN SUMMER OF IRAQ - Hasan, Khalid Hamid (Diyala Agricultural Sciences Journal, 2013)
This study was conducted to determine the productive performance of Japanese quail during summer season in Iraq along the period 10 July 2011 to 25 Sept. 2011 . The flock consist of 60 one day old chicks and reared in three boxes with dimensions 50* 50* 100 Cm., the measurements included the following traits : Live body weight , gain body weight , Uniformity , Age at sexual maturity , Egg weight , Shell weight , Shell thickness , Egg shape index , Chick weight / Egg weight percentage and calculated correlation coefficients and regression coefficients between some traits of the study . The results inducted that , the mean chick weight and its uniformity were 7.24 g and 56.25 % respectively . The egg weight , shell weight , shell thickness , shape index , chick weight / egg weight , age at sexual maturity were 9.54 g , 1.23 g , 0.25 mm , 79.19 % , 75.89 % , 40.63 day , there were highly significant correlation coefficients between shell weight and each of shell thickness and shape index ( 0.45 and – 0.68 respectively ) , also there were significant regression coefficients between chick weight and each of egg weight and shape index ( 0.88 and – 0.45 respectively )